2019
DOI: 10.1080/21691401.2019.1638795
|View full text |Cite|
|
Sign up to set email alerts
|

Ras-AKT signaling represses the phosphorylation of histone H1.5 at threonine 10 via GSK3 to promote the progression of glioma

Abstract: View related articles View Crossmark data Citing articles: 3 View citing articles Ras-AKT signaling represses the phosphorylation of histone H1.5 at threonine 10 via GSK3 to promote the progression of glioma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…For example, Liu et al and Li et al indicated that Ras-PI3K pathway activation could reduce the acetylation of histone H3 at lysine 56 (H3 K56ac ) and then promote the proliferation and migration of HeLa cells, as well as the occurrence and development of uveal melanoma [29,30]. Moreover, Sang et al discovered that Ras-AKT pathway activation could inhibit the phosphorylation of histone H1.5 at threonine 10 (H1.5 T10ph ) and then promote the development of glioma [31]. We could propose that Ras-PI3K-AKT pathway activation might take part in the regulation of the number of histone modifications in cancer cells, which may form a very intricate regulatory Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al and Li et al indicated that Ras-PI3K pathway activation could reduce the acetylation of histone H3 at lysine 56 (H3 K56ac ) and then promote the proliferation and migration of HeLa cells, as well as the occurrence and development of uveal melanoma [29,30]. Moreover, Sang et al discovered that Ras-AKT pathway activation could inhibit the phosphorylation of histone H1.5 at threonine 10 (H1.5 T10ph ) and then promote the development of glioma [31]. We could propose that Ras-PI3K-AKT pathway activation might take part in the regulation of the number of histone modifications in cancer cells, which may form a very intricate regulatory Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…That would require a detailed molecular analysis of the chromatin alterations/epigenetic modifications occurring at the H1.5 promoter. The epigenetic changes and protein interactions occurring on the HIST1 locus in general, are usually omitted in studies investigating H1.5 expression [ 10 , 16 , 20 , 21 ]. Therefore, the connections of H1.5 expression to cellular processes—differentiation and disease—remain unknown.…”
Section: A Promiscuous Protein—h15’s Many Interaction Partnersmentioning
confidence: 99%
“…That the latter is necessary to experiments involving linker histones has been exemplified by Sang et al . [ 21 ], who investigated the role of site-specific phosphorylation of H1.5 in Ras-mediated glioma progression. As it is currently disputed, whether this paper is lacking scientific integrity, we present the results below but advise the reader to take them as a starting point for thought [ 40 ].…”
Section: Differentiation Gone Wrong—h15’s Role In Cancermentioning
confidence: 99%
See 2 more Smart Citations